Deposit Interest Rates and Amount of Time Deposit Funds - Arfah, Aryati; Muslim, Muslim (Advances in Economics & Financial Studies, 2023)
This study aims to determine the effect of deposit interest rates on the amount of time deposits at PT Bank Rakyat Indonesia Makassar Branch. The data source used is secondary data, in this case the data and financial statements of PT Bank Rakyat Indonesia Makassar Branch for a year, including reports on deposit interest rates of PT Bank Rakyat Indonesia Makassar Branch. This research uses data collection techniques through field studies. The analysis method used is simple linear regression using the SPSS 16.0 for Windows program. Based on hypothesis testing using the F test it is concluded that the term interest rate does not have a positive influence on time deposit funds. And based on the partial test (t) it is concluded that the term interest rate has no significant effect on time deposit funds.